Problem Solving Geometry of Visualization, Analysis, and Informal deduction subject based on SOLO Taxonomy - Asep Rosadi; Siti M. Amin; Raden Sulaiman (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2018)
Problem solving is a way which will be conducted someone by employing acquired skills, knowledge, and understanding in order to solve certain problem. Problem solving stages which attained in this research is according to Polya which encompasses comprehending problem, arranging plan completion, and rechecking the result. Mathematics concept understanding is required in order to solve the problem. SOLO Taxonomy classifies the subject’s ability of solving problem into five different level, prestructural, unistructural, multistructural, relational, and extended abstract. The aim of this research is to describe geometry problem solving of visualization, analysis and informal deduction according to SOLO Taxonomy. Additionally, qualitative descriptive method is used to analyze the data. Subjects of this research are subjects who possess high mathematics thinking ability of visualization geometry, analysis and informal deduction. Besides, the type of data collection technique uses problem solving geometry test and interview. According to the result of research, subjects who possess in visualization geometry thinking level to solve the problem tend to use the aspect of unistructural level of SOLO Taxonomy. Then, subjects with analysis geometry thinking level to solve the problem mostly use multistructurallevel of SOLO Taxonomy. Lastly, subjects who own informal deduction geometry thinking level to solve the problem apparently use relational level of SOLO Taxonomy.